2007
DOI: 10.1002/pat.802
|View full text |Cite
|
Sign up to set email alerts
|

Poly(propylene) with micro‐fillers—the way of enhancement of toughness

Abstract: Commercially available poly(propylene)(PP) (MOSTEN, MFR ¼ 4 g/10 min) supplied by a Czech company Chemopetrol Litvínov and precipitated calcium carbonate (CaCO 3 ) was used for this study. The CaCO 3 particles were coated with surface agent improving their dispersion.The effect of the PP structure, the volume content and surface coating of particles on the decisive mechanical properties (dynamic modulus of elasticity and dynamic fracture toughness) was evaluated by means of dynamic mechanical thermal analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The advantageous potential of micro fillers is well known and proven approach for material enhancements in industry as well as in the appliance industry 5, 8, 22…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantageous potential of micro fillers is well known and proven approach for material enhancements in industry as well as in the appliance industry 5, 8, 22…”
Section: Resultsmentioning
confidence: 99%
“…Research works on all‐PP composites has shown so far that the creep behavior PP/PP composites depends strongly on stress, temperature, void content, (fiber) loading, and (fiber) dimensions 6, 8…”
Section: Poly(propylene) Composites and Evaluation Of Polymer Productmentioning
confidence: 99%
“…= 39 GPa (Kucera and Nezbedova, 2007 (Raman, 1997) It is at the very least interesting to note the considerably high magnitude of difference in the predictions that result from the modifications made in Section 2. The Reuss model is sometimes taken to be a reasonable 'lowest limit' estimator for the Young modulus in particulate composites provided the particle fraction is below 0.3 (Rothon, 2003).…”
Section: Ermentioning
confidence: 96%
“…For the experimental work, representative material samples were used for calculating E c , the Voigt, Reuss, Bert and McAdam models in conjunction with the mercury porosimetry results and the particle size distribution statistics. A value of 39 GPa from Kucera and Nezbedova (2007) was assigned to the particles and the binder was taken to be 4 MPa based on Raman (1997), which was furthermore confirmed through experimental testing. The statistical modelling provided all the necessary parameters for calculating the E c (Eq.…”
Section: Comparison Of Eq (5) Voigt Reuss Bert and Mcadam Models mentioning
confidence: 99%
“…There are many studies related to the improvement of the mechanical properties of PP, for example, the addition of elastomer particles, such as SEBS improves their impact resistance but significantly reduces its stiffness and yield strength [1–4]. Improvement in impact resistance of PP was obtained with the addition of calcium carbonate (CaCO 3 ) [5]. Adding glass fibers to PP is relatively easy and very effective for reinforcing tensile, flexural, and impact properties [6–8].…”
Section: Introductionmentioning
confidence: 99%